The productivity of return migrants: The case of China's Sea Turtles - Wei Sun (IZA Journal of Migration, 2013)
This paper explores the productivity differential between return migrants ('Sea Turtles') and non-migrants through a case study of China's venture capital (VC) industry. I find that even after correcting for selection bias, return venture capitalists are less productive than comparable non-migrants in targeting promising projects and/or providing value-added services. Given that the VC industry is a useful laboratory in which to look at the performance of return migrants and China's economic development, I discuss why the presumably better human capital accumulated overseas does not translate into productivity in the Chinese market, and how related policies could reverse this situation in the long run.
Keywords: F22; G24; O15; 330; return migrants; venture capital; China